2007
DOI: 10.1590/s1519-69842007000100025
|View full text |Cite
|
Sign up to set email alerts
|

Small mammal populations of an agroecosystem in the Atlantic Forest domain, southeastern Brazil

Abstract: This study reports 2 years of the population dynamics and reproduction of a small mammal community using the removal method. The study was conducted in a rural area of the Atlantic Forest, in Sumidouro, Rio de Janeiro State, Brazil. The population sizes, age structure and reproduction were studied for the four most common species in the study area. The overall diversity was 1.67 and ranged between 0.8 to 1.67. The species richness was 13 considering the whole study. The most abundant species were the rodents N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
2
21
0
10
Order By: Relevance
“…Because superciliaris has not, to our knowledge, been recognized as a valid taxon for almost two centuries, it would seem pointless to use this name to replace quica, the application of which is undisputed. Therefore, to fix the application of Didelphys superciliaris Olfers for the species that occurs in eastern Amazonia, we select as neotype a specimen in the American Museum of Natural History (AMNH 203348) consisting of the skin and skull of an adult male collected by personnel from the Instituto Oswaldo Cruz on 6 December 1960 near "Capim" (= São Domingos do Capim; 1°40´S, 47°47´W; Paynter and Traylor, 1991) at Km 92 on highway BR 14,Pará,Brazil. Habitats: Within the Atlantic Forest biome or ecoregion (Mata Atlântica), Philander quica seems to be eurytopic, occurring in a wide range of vegetation types including mature lowland rainforest (formerly the dominant climax vegetation of southeastern Por, 1992), submontane forest, secondary growth, agricultural fields, and coastal restinga scrub (Cerqueira et al, 1993;Bergallo, 1994;Bonvicino et al, 1997;Passamani et al, 2000;D' Andrea et al, 2007 Philander canus (Osgood, 1913) Metachirus canus Osgood, 1913: 96; type locality Peru, San Martín, Moyobamba (6°03′ S, 76°58′ W; Stephens and Traylor, 1983). Metachirus opossum crucialis Thomas, 1923: 604 Although the skin is well preserved, the skull is broken and incomplete (the left zygomatic arch, the left squamosal, and the left bulla are all missing).…”
Section: Fig 14 Lateral View Of P2-m1 Of Philander Canus (A Amnh 2mentioning
confidence: 99%
“…Because superciliaris has not, to our knowledge, been recognized as a valid taxon for almost two centuries, it would seem pointless to use this name to replace quica, the application of which is undisputed. Therefore, to fix the application of Didelphys superciliaris Olfers for the species that occurs in eastern Amazonia, we select as neotype a specimen in the American Museum of Natural History (AMNH 203348) consisting of the skin and skull of an adult male collected by personnel from the Instituto Oswaldo Cruz on 6 December 1960 near "Capim" (= São Domingos do Capim; 1°40´S, 47°47´W; Paynter and Traylor, 1991) at Km 92 on highway BR 14,Pará,Brazil. Habitats: Within the Atlantic Forest biome or ecoregion (Mata Atlântica), Philander quica seems to be eurytopic, occurring in a wide range of vegetation types including mature lowland rainforest (formerly the dominant climax vegetation of southeastern Por, 1992), submontane forest, secondary growth, agricultural fields, and coastal restinga scrub (Cerqueira et al, 1993;Bergallo, 1994;Bonvicino et al, 1997;Passamani et al, 2000;D' Andrea et al, 2007 Philander canus (Osgood, 1913) Metachirus canus Osgood, 1913: 96; type locality Peru, San Martín, Moyobamba (6°03′ S, 76°58′ W; Stephens and Traylor, 1983). Metachirus opossum crucialis Thomas, 1923: 604 Although the skin is well preserved, the skull is broken and incomplete (the left zygomatic arch, the left squamosal, and the left bulla are all missing).…”
Section: Fig 14 Lateral View Of P2-m1 Of Philander Canus (A Amnh 2mentioning
confidence: 99%
“…Human populations were also diagnosed and treated. With this design, we obtained results that have enabled us to raise the small mammal fauna of the area (D'Andrea et al, 1999), understand the pattern of population dynamics of the water-rat (Bonecker et al, 2009;D'Andrea et al 2007;Gentile et al 2000) and its habitat use (Gentile & Fernandez 1999), understand aspects of the relationship between S. mansoni and N. squamipes Gentile et al, 2006), and adapt procedures and techniques to local particularities. In Pamparrão, which is a low endemicity area, the population dynamic study of the waterrat showed that it reproduced throughout the year, predominantly during the rainy periods.…”
Section: Eco-epidemiologic Monitoring -The Rodent As a Focus Transmismentioning
confidence: 99%
“…A reprodução pode ocorrer ao longo de todo o ano, como no Planalto Atlântico de São Paulo (Gaspar 2005), mas geralmente é concentrado de julho/agosto até fevereiro/março/abril em várias populações (D'Andrea et al 1999, Gentile et al 2000, Graipel e Santos-Filho 2006, D'Andrea et al 2007, Kajin et al 2008. As fêmeas começam a se reproduzir com aproximadamente cinco meses de idade , Kajin et al 2008, as fêmeas nascidas em um período reprodutivo já podem se reproduzir no seguinte ), e podem ocorrer pelo menos duas ninhadas por período reprodutivo para uma mesma fêmea (D'Andrea et al 1999, Graipel e Santos-Filho 2006, Kajin et al 2008.…”
Section: Reproduçãounclassified
“…A densidade média foi de 5 indivíduos/ha em área de Cerrado (Alho et al 1986) e 2,72 ind/ha em área de restinga no Rio de Janeiro (Cerqueira et al 1983). A abundância pode ser mais alta durante o inverno (Fonseca e Kieruff 1989, D'Andrea et al 2007). …”
Section: Ordem Rodentiaunclassified
See 1 more Smart Citation